PENGARUH RISIKO SISTEMATIS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SERTA DAMPAKNYA TERHADAP PERTUMBUHAN LABA DAN KOEFISIEN RESPON LABA (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Darwanis Darwanis; Dana Siswar; Arie Andina (Program Magister Akuntansi Unsyiah, 2013)
The objective of the study is to examine (1) the influence of systematic risk on corporate social responsibility (CSR) disclosure; (2) the influence of systematic risk and CSR disclosure on earnings growth simultaneously; (3) the influence of systematic risk on earnings growth; (4) the influence of CSR disclosure on earnings growth; (5) the influence of systematic risk, CSR disclosure and earnings growth on earnings response coefficient simultaneously; (6) the influence of systematic risk on earnings response coefficient; (7) the influence of CSR disclosure on earnings response coefficient; (8) the influence of earnings growth on earnings response coefficient.The object of populations used in this study are manufacturing industries listed in The Indonesia Stock Exchange for period 2008 - 2009. The data used are annual report, sustainability report, financial report, and stock’s information. The study tested hypothesis by using path analysis method which operated by SPSS 17 statistic software.The results of this study indicate that systematic risk has influence on corporate on social responsibility disclosure. Its meant that the higher systematic risk, the more CSR informations disclosed by the firms. Systematic risk and CSR disclosure have influence on earnings growth simultaneously. This impact shows that the reducting of systematic risk and the implementing of CSR activities as the sustainability strategic, will aim to increase the earnings growth rate. Partially, systematic risk has a negative influence and CSR disclosure has a positive influence on earnings growth. Systematic risk, CSR disclosure and earning growth have influence on earnings response coefficient simultaneously. It meant that investor will respons systematic risk, CSR disclosure and earning growth as factors influenced the informativeness of earnings. Partially systematic risk, CSR disclosure and earning growth have positive influence on earnings response coefficient.Keywords: Earnings Response Coefficient, Earnings Growth, Corporate Social Responsibility Disclosure, Systematic Risk.